Lipid production from biofilms of Marinobacter atlanticus in a fixed bed bioreactor - Matthew D. Yates; Rebecca L. Mickol; Joseph S. Tolsma; Maryssa Beasley; Jamia Shepard; Sarah M. Glaven (Microbial Cell Factories)
Abstract Background Biotechnologies that utilize microorganisms as production hosts for lipid synthesis will enable an efficient and sustainable solution to produce lipids, decreasing reliance on traditional routes for production (either petrochemical or plant-derived) and supporting a circular bioeconomy. To realize this goal, continuous biomanufacturing processes must be developed to maximize productivity and minimize costs compared to traditional batch fermentation processes. Results Here, we utilized biofilms of the marine bacterium, Marinobacter atlanticus, to produce wax esters from succinate (i.e., a non-sugar feedstock) to determine its potential to serve as a production chassis in a continuous flow, biofilm-based biomanufacturing process. To accomplish this, we evaluated growth as a function of protein concentration and wax ester production from M. atlanticus biofilms in a continuously operated 3-D printed fixed bed bioreactor. We determined that exposing M. atlanticus biofilms to alternating nitrogen-rich (1.8 mM NH4 +) and nitrogen-poor (0 mM NH4 +) conditions in the bioreactor resulted in wax ester production (26 ± 5 mg/L, normalized to reactor volume) at a similar concentration to what is observed from planktonic M. atlanticus cells grown in shake flasks previously in our lab (ca. 25 mg/L cell culture). The wax ester profile was predominated by multiple compounds with 32 carbon chain length (C32; 50–60% of the total). Biomass production in the reactor was positively correlated with dilution rate, as indicated by protein concentration (maximum of 1380 ± 110 mg/L at 0.4 min−1 dilution rate) and oxygen uptake rate (maximum of 4 mmol O2/L/h at 0.4 min−1 dilution rate) measurements at different flow rates. Further, we determined the baseline succinate consumption rate for M. atlanticus biofilms to be 0.16 ± 0.03 mmol/L/h, which indicated that oxygen is the limiting reactant in the process. Conclusion The results presented here are the first step toward demonstrating that M. atlanticus biofilms can be used as the basis for development of a continuous flow wax ester biomanufacturing process from non-sugar feedstocks, which will further enable sustainable lipid production in a future circular bioeconomy